Sono-Enzymatically Embedded Antibacterial Silver-Lignin Nanoparticles on Cork Filter Material for Water Disinfection - Bermeo, Lizeth (2022)
Providing clean drinking water is a great challenge worldwide, especially for low-income countries where the access to safe water is limited. During the last decade, new biotechnological approaches have been explored to improve water management. Among them, the use of antimicrobial nanoparticles for designing innovative centralized and decentralized (point-of-use) water treatment systems for microbial decontamination has received considerable attention. Herein, antimicrobial lignin capped silver nanoparticles (AgLNP) were embedded on residual cork pieces using high-intensity ultrasound coupled with laccase-mediated grafting to obtain biofunctionalized nanomaterial. The developed AgLNP-coated cork proved to be highly efficient to drastically reduce the number of viable Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus in liquid medium. Additionally, the coated-cork was characterized using FTIR-ATR spectroscopy and SEM imaging, and further used as a filter bed in a point-of-use device for water disinfection. The constructed water filtering system significantly reduced the amount of viable E. coli and resistant Bacillus cereus spores from filtered water operating at increasing residence times of 1, 4, 6, 16, 24, and 48 h. Therefore, the presented results prove that the obtained cork-based antimicrobial nanocomposite material could be used as a filtering medium for the development of water filtration system to control pathogen dissemination.